Research and Realization of Ethernet Service MEF 2.0 Certification - Quan Lu; Tong Lin; Xin Hu; Xuan Zhang (Dianxin kexue)
MEF Carrier Ethernet（CE）2.0 has been widely concerned and supported by international major telecom service providers.It has become new generation standard of Ethernet service interoperability and transparent management.By researching MEF CE 2.0 related standards，methods and key technical details in depth，related service definition，operation flow，network topology，test items and practical application of CE 2.0 authentication testing were summarized.